Natural restoration in an unmanaged Eucalyptus sp plot: a case study (Research, Society and Development, 2022)
This study aimed to evaluate if a Eucalyptus plot that has not been managed for 20 years is in the process of restoration. The survey was carried out in the Private Natural Heritage Reserve – RPPN – Botujuru, in Mogi das Cruzes, SP. Six 100 m transects were installed, with four 50 m² circular plots (3.99 m radius) and four 1 x 10 m rectangular plots. Data were classified into regenerating stratum (up to 1,3 m), stratum 2 (girth at breast height (PAP) ≤ 15 cm) and stratum 3 (PAP > 15 cm). In the results there was a difference in the composition of the strata. While the pioneers showed a high importance value in the upper strata, in the regenerating stratum the families and species recruited are mainly the non-pioneers. Only in stratum three were individuals of the Eucalyptus species found, which shows that it does not act as an invasive species in the study area. It is concluded that due to the diversity found in the understory, the replacement of species in the strata and the abundance of non-pioneer species, the restoration process is taking place.